Typologia psychologiczna Carla Gustawa Junga a glottodydaktyka - Wojtynek-Musik, Krystyna (Neofilolog, 2010)
According to C.G. Jung, people, including teachers and students, can be divided into four personality types, depending on the dominating psychological function. These functions are thinking, feeling, sensation and intuition which can be further subdivided into introverts and extraverts. The awareness of this psychological diversity may spare teachers and their students a great number of disappointments and misunderstandings and may also help them to create their own style of learning and working on the second language.